Analysing Factors Affecting Green Construction Productivity: Exploratory Factor Analysis - Mahat, Noor Aisyah Asyikin; Adnan, Hamimah; Mohamad Yusuwan, Norazian (International Journal of Sustainable Construction Engineering and Technology, 2022)
Construction sector productivity is substantial significance for the government and policymakers because it creates a competitive industry environment as well as determines a nationâ€™s expectancy. Addressing the factors influencing productivity especially in Green Construction Project (GCP) is essential and its significantly need to align with the target goal in Malaysia Green Technology Master Plan (2017â€“2030). In lieu to the scenario, this research aims to identify the important factors affecting the productivity of GCP, by evaluating the criticality factors that may contribute to project productivity. Based on the previous studies, five (5) key component factors were identified with a total of forty-four (44) associated items. The key component factors can be broadly categorized into • i) Project, ii) Manpower, iii) Management, iv) Technical and v) External aspect. These factors with their associated items, are then used to develop questionnaire survey to gather data. The Exploratory Factor Analysis (EFA) was employed to the collected data which emphasize to the five (5) component factors with forty-four (44) items affecting green construction productivity with the total variance percentage is 72.113%. Each of the components consists of at least seven (7) variables, so the components complied with the requirement that each component must have at least three variables. According to the findings, the KOM (Kaiser-Meyer-Olkin Measure of Sampling Adequacy) is 9, which is very similar to 1. Each factor loading variable is greater than 0.4 indicating that all components satisfied the Factor Analysis rule. The highest Eigenvalue is on Project Factors (18.175), and the lowest is External Factors (1.154). It is important to understand all key factors affecting the construction productivity, so that the industry practitioners can effectively strategies a plan to improve the productivity in GCP, for prompt delivery of construction projects with lower cost, higher quality and remarking sustainability.